Knowledge of Basic Life support in Post Graduate Residents in two Teaching Hospitals - Mehwish Sharif, Tariq Javaid, Aimen Sajjad, Maria Shireen, Rani Saba Urooj, Abdul Hafeez (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cardiopulmonary resuscitation (CPR) knowledge and training among junior doctors is very important as the junior doctor is mostly the first one to attend the patients in emergency room. Unfortunately, they don’t have enough knowledge. Healthcare professionals need to have hands-on practice regularly in order to retain the BLS skills. Aim: To determine the frequency of adequate knowledge of basic life support among Post graduate residents. Method:A Descriptive, Cross-sectional study was conducted from November 2017 to May 2018 in the Children’s Hospital Lahoreand from June 2022to August 2022 in Government Kot Khawaja Saeed Teaching Hospital, Lahore. A total of 96doctors of all 4 years of postgraduate training program of either genderwere included. A questionnaire was prepared. It included demographic data and BLS knowledge assessment. It was distributed to participants who met the inclusion criteria. It did not contain the name of the participant and confidentiality was maintained. Questionnaire was collected back after the completion and knowledge score was noted as described in questionnaire. Score >8 was taken as adequate knowledge. Results: Mean age was 28.76 ± 2.29 years. Out of 96 participants, 70 were from Children Hospital and 26 from Govt. Kot Khawaja Saeed Teaching Hospital KEMU, 50(52.08%) were males and 46(47.92%) were females. The male to female ratio is 1.1:1. Mean time duration since BLS course attended was 9.12±4.54 months. Mean score was 11.78±3.98. This study has shown frequency of adequate knowledge of basic life support among pediatric residents in 57(59.38%) participants and remaining 39(40.62%) participants showed no adequate knowledge. Conclusion: It is concluded that frequency of adequate knowledge of basic life support among postgraduate residents is good. Keywords: Basic life support (BLS), Pediatric Advanced Life Support, residents, adequate knowledge.